An Intelligent Power Management Investigation for Stand-alone Hybrid System Using Short-time Energy Storage - Ben Slama Sami (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Stand-alone Hybrid systems become appreciating issues that ensure the required electricity to consumers. The development of a stand-alone Hybrid system becomes a necessity for multiple applications The enhance energy security. To achieve this objective, we have proposed an accurate dynamic model using Multi-Agent System (MAS) in which a solar energy System (SES) serves as the main load supply, an energy Backup System (ERS) is based on a fuel cell and Electrolyzer for long-term energy storage and an Ultra Capacitor (UCap) storage system deployed as a short-time storage. To cooperate with all systems, an Intelligent Power Management (IPM) based on a specific MAS is included. Thus, to prove the performance of the system, we tested and simulated it using the Matlab/Simulink environment.